2018
DOI: 10.1002/prot.25497
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of nanobody sequence and structure data

Abstract: Nanobodies are a class of antigen‐binding protein derived from camelids that achieve comparable binding affinities and specificities to classical antibodies, despite comprising only a single 15 kDa variable domain. Their reduced size makes them an exciting target molecule with which we can explore the molecular code that underpins binding specificity—how is such high specificity achieved? Here, we use a novel dataset of 90 nonredundant, protein‐binding nanobodies with antigen‐bound crystal structures to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 39 publications
(84 reference statements)
12
164
0
Order By: Relevance
“…Llama nanobodies have been shown to tether to early endosomes and to mitochondria (Traub, 2019), be used for diagnostics (Shriver-Lake et al, 2018), be used for design of cancer immunotherapeutics (Hussack et al, 2018;Bannas and Koch-Nolte, 2018;Rossotti et al, 2019) and have been approved for passive immunotherapy (Sheridan, 2019). Our current finding, that llama nanobodies can be post-translationally deiminated may shed some light on their observed structural variation which still remains to be fully explained as sequence alignment does not fully elucidate their diversity (Mitchell and Colwell, 2018). As a structurally analogous immunoglobulin in shark, new antigen receptor (NAR) (Greenberg et al, 1995;Barelle et al, 2009;Flajnik and Dooley, 2009;De Silva et al, 2019) was recently also found to be deiminated (Criscitiello et al, 2019), our current finding may provide novel insights into function of these immune proteins and be useful for refinement in therapeutic nanobody development.…”
Section: Discussionmentioning
confidence: 85%
“…Llama nanobodies have been shown to tether to early endosomes and to mitochondria (Traub, 2019), be used for diagnostics (Shriver-Lake et al, 2018), be used for design of cancer immunotherapeutics (Hussack et al, 2018;Bannas and Koch-Nolte, 2018;Rossotti et al, 2019) and have been approved for passive immunotherapy (Sheridan, 2019). Our current finding, that llama nanobodies can be post-translationally deiminated may shed some light on their observed structural variation which still remains to be fully explained as sequence alignment does not fully elucidate their diversity (Mitchell and Colwell, 2018). As a structurally analogous immunoglobulin in shark, new antigen receptor (NAR) (Greenberg et al, 1995;Barelle et al, 2009;Flajnik and Dooley, 2009;De Silva et al, 2019) was recently also found to be deiminated (Criscitiello et al, 2019), our current finding may provide novel insights into function of these immune proteins and be useful for refinement in therapeutic nanobody development.…”
Section: Discussionmentioning
confidence: 85%
“…In these structures, the binding affinity is mainly contributed by the flexible CDR3 interaction with the antigen, whereas CDR1 and CDR2 provide an additional interaction force [27]. In these structures, the binding affinity is mainly contributed by the flexible CDR3 interaction with the antigen, whereas CDR1 and CDR2 provide an additional interaction force [27].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, there is an increasing awareness that nanobodies are more differentiated in their structure than initially thought. Specifically, they do not possess a single highly uniform paratope shape but rather may build it combining a large spectrum of different 3D conformations which can involve also the framework residues and confer them several alternative surfaces for interacting with the antigens [119,120,133]. Despite the lack of experimental reports, it can be anticipated that the folding requirements of the different VHH sub-types might be variable as well and, consequently, reference structures used for modeling must be selected with accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nanobodies are suitable for both X-ray crystallography and NMR analyses, therefore several structures are now available for simulating the 3D conformation of new candidates. Recently, the structural information has been also used to understand the specificities of the binding patterns existing between antigens and VHHs [119,120]. This fortunate combination of structural data availability and short sequence stimulated the search for modeling approaches able to suggest mutants performing better than the nanobodies initially isolated by biopanning [121].…”
Section: In Silico Optimizationmentioning
confidence: 99%